The works of Mr. Richard Hooker - Hooker, Richard (Joseph Addison Alexander library., 1825)
v. 1. Life of Mr. Richard Hooker. Of the laws of ecclesiastical polity, books I-V.--v. 2. Of the laws of ecclesiastical polity, books V (cont'd)-VIII. A supplication made to the Council by Master Walter Travers. Master Hooker's answer to the supplication that Master Travers made to the Council. A learned discourse of justification, works, and how the foundation of faith is overthrown. A learned sermon of the nature of pride. A remedy against sorrow and fear, delivered in a funeral sermon. Of the certainty and perpetuity of faith in the elect, especially the prophet Habakkuk's faith. Two sermons upon part of St. Jude's Epistle. A sermon upon Matt. VII. 7, 8.